THE SYSTEMATIC REVIEW OF STEM CELL THERAPY FOR STRESS URINARY INCONTINENCE - Nanda Satya Pratama, Muhammad; Himawan, Herinto (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
The aim: This study aims to show stem cell therapy for stress urinary incontinence. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up to date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database the results of our search brought up 133 articles, whereas the results of our search on SagePub brought up 54 articles. The results of the search conducted for the last year of 2013 yielded a total 89 articles for PubMed and 41 articles for SagePub. The result from title screening, a total 9 articles for PubMed and 15 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria.Conclusion: Comprehensive comparisons between stem cell-based approaches and existing therapies are a prerequisite to rendering stem cell treatment as the predominant strategy for treating intractable urological disorders in the future.